2022
DOI: 10.3389/fimmu.2022.901697
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hepatic Lipid Metabolism and Immune Function During the Development of Collagen-Induced Arthritis

Abstract: The liver is essential for metabolic and immune functions and has been linked to systemic inflammatory diseases. However, the role of the liver is still elusive during the development of rheumatoid arthritis (RA), although there have been indeed some reports. We used label-free quantitative proteomics and experimental verification in this study to reveal the hepatic lipid metabolism and immune function during collagen-induced arthritis (CIA) development. The proteomics results revealed that the role of the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…There is evidence of elevated immune cell infiltration in the livers, kidneys, and lungs of arthritic mice (35,36). Inhibition of PAD4 could therefore not only be beneficial to the primary disease but several collateral comorbidities of RA as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence of elevated immune cell infiltration in the livers, kidneys, and lungs of arthritic mice (35,36). Inhibition of PAD4 could therefore not only be beneficial to the primary disease but several collateral comorbidities of RA as well.…”
Section: Discussionmentioning
confidence: 99%
“…Histological analysis suggested that the functional improvement was likely because of the prevention of myocardial hypertrophy and myocardial fibrosis (Fig 5D and F). Mice treated with JBI-589 had lower heart weight-to-tibia length ratio (9 [±2] mg/mm versus 11 [±2] mg/mm; P = 0.004) and reduced LVM measured by echocardiography (33 [27][28][29][30][31][32][33][34][35][36][37][38][39] mg versus 74…”
Section: Treatment With An Orally Available Pad4 Inhibitor Preserves ...mentioning
confidence: 99%
“…Establishment and Evaluation of CIA: The RA rat models were established using previously described methods and protocols using bovine type II collagen and complete Freund's adjuvant. [27] 24 male Sprague-Dawley rats were randomly divided into four groups as follows (n = 6): Control, CIA, free psoralen, and psoralen gel groups. The free psoralen and psoralen gel groups were treated via intra-articular injection, in which the psoralen gel group was injected with 50 µL psoralen gel, and the free psoralen group was injected the same dose of psoralen without the hydrogel sustained-release system.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, RA is associated with increased incidence and mortality rates of CVD. In recent times, the interplay between lipid metabolism and RA has garnered increasing attention (4). Conventional synthetic disease-modifying antirheumatic drugs (DMARDs) play a crucial role in the treatment of inflammatory arthritides, including RA.…”
Section: Introductionmentioning
confidence: 99%